2022
DOI: 10.3389/fendo.2022.1081185
|View full text |Cite
|
Sign up to set email alerts
|

The potential mechanisms and application prospects of non-coding RNAs in intervertebral disc degeneration

Abstract: Low back pain (LBP) is one of the most common musculoskeletal symptoms and severely affects patient quality of life. The majority of people may suffer from LBP during their life-span, which leading to huge economic burdens to family and society. According to the series of the previous studies, intervertebral disc degeneration (IDD) is considered as the major contributor resulting in LBP. Furthermore, non-coding RNAs (ncRNAs), mainly including microRNAs (miRNAs), long noncoding RNAs (lncRNAs) and circular RNAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 109 publications
0
10
0
Order By: Relevance
“…LFH is a major cause of LSS, leading to remarkable disability and morbidity [ 2 ]. Growing evidence shows that noncoding RNAs, including lncRNAs, play a role in the development and progression of various disorders, including spinal diseases [ 9 , 29 ]. Previous studies have investigated molecular mechanisms underlying LFH; however, the role of lncRNAs in LFH progression is only partially understood [ 22 , 23 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…LFH is a major cause of LSS, leading to remarkable disability and morbidity [ 2 ]. Growing evidence shows that noncoding RNAs, including lncRNAs, play a role in the development and progression of various disorders, including spinal diseases [ 9 , 29 ]. Previous studies have investigated molecular mechanisms underlying LFH; however, the role of lncRNAs in LFH progression is only partially understood [ 22 , 23 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was found that the levels of global Mechanical, traumatic, genetic and nutritional factors can contribute to the progression of IDD. 43 Significantly, aging is considered as one of important factors leading to the pathogenesis of IDD. 44 The aging promoting the progression of IVD degeneration and NP cell senescence.…”
Section: Discussionmentioning
confidence: 99%
“…The etiologies of IDD remain quite complicated. Mechanical, traumatic, genetic and nutritional factors can contribute to the progression of IDD 43 . Significantly, aging is considered as one of important factors leading to the pathogenesis of IDD 44 .…”
Section: Discussionmentioning
confidence: 99%
“…LBP makes the individuals suffering torment and increases economic and social burdens, especially in the health care field 7,8 . To the best of our knowledge, the normal intervertebral disc (IVD) in mammals is composed of three integral parts: the nucleus pulposus (NP) cells, annulus fibrosus (AF) and cartilage endplates 4,9 . Long‐term overloading, along with factors such as injury, smoking and ageing, can lead to IVD degeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that various epigenetic modifications, including DNA methylation, histone modifications, RNA methylation (m 6 A) and mitochondrial quality control, play crucial roles in the pathogenesis of IVD degeneration 10,12 . NP cells are critical for sustaining the integrity of the IVD and function by producing the ECM, which is required for cell differentiation and proliferation 9 . In addition, many other factors, including environmental and genetic factors (e.g.…”
Section: Introductionmentioning
confidence: 99%